Long-wave light sensitivity of a thin film system based on PbI₂ and Cu - Sopinskyy, M.V.; Mynko, V.I.; Olkhovik, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Photostimulated interaction in a sandwich-like thin film system based on PbI₂ and Cu (photodoping effect) makes it possible to use the system as a recording medium. On the other hand, since the layer consisting of copper nanoparticles embedded into the PbI₂ matrix is formed as a result of photodissolution of Cu film, this effect can be considered as an original way to produce nanocomposites. In this work, long-wave sensitivity of the PbI₂–Cu₂O–Cu system has been studied in conjunction with the structure of the PbI₂ film. It has been established that, in the hν < Eg (PbI₂) spectral region the light absorption in PbI₂ film and the metal film photodissolution rate are higher for the less compact (more porous) PbI₂ films.